Violencia psicológica y su influencia en el comportamiento de un adolescente - Rodriguez García, Thaylee Joaida (2020)
In this case study we worked with the topic of psychological violence and its influence on adolescent behavior in the Fausto Misael Olalla Gaybor Educational Unit starting from the conceptualization of the variables to know that it implies psychological violence since it is a subject that its meaning is still unknown in its entirety in our society as it manifests itself in several ways such as: abuse verbal, intimidation, abuse of power, indifferent towards the other person, emotional abuse among others these affect in different ways in our case we want to know how it affects in adolescent behavior. and manifestation of their behavior. Making a therapeutic plan to modify their unacceptable behaviors for that with the use of various techniques and application tools, such as medical history, interviews and tests as the test of the person in the rain and the MACI, with the cognitive-behavioral approach looking for possible solutions to the problem of adolescents in their behavior and building healthy emotional bonds.